Strengthening social skills: developing a social competence intervention for physical education using intervention mapping—protocol paper - Iris Schüller; V. Vanessa Wergin; Filip Mess (Frontiers in Psychology)
IntroductionThe promotion of social competences using multi-method approaches is an understudied area in education and psychology. This study addresses the gap by developing and presenting a program to enhance social competences using theory-derived program and assessment designs.Materials and equipmentBartholomew’s Intervention Mapping (IM) approach, initially used for health promotion, was innovatively applied to a psychological and educational context. The development process and implementation challenges are presented in this article.MethodsThe six-step IM process was adapted to create a comprehensive program design that models social behavior, specifically for Physical Education in schools. The program targets perceptive-cognitive, emotional-motivational, and behavioral components of social competence, along the social competence model by Kanning. Results on effect sizes have yet to be calculated.DiscussionThe IM process was time-consuming and extensive but provided a systematic structure, methodological quality, and traceability of effects. Future adaptations of this program could include extensions to different situational contexts and specific need groups, such as classes with a history of bullying or psychological conditions. This study contributes valuable insights into using the IM approach for promoting behavioral change in a systematic and evidence-based manner.